SEGMENTASI PASAR KONSUMEN MAKANAN DI JAKARTA, INDONESIA DENGAN PENDEKATAN FOOD-RELATED LIFESTYLE - Chandra Cipta Ishano (AGRIBUSINESS JOURNAL, 2017)
Recently, the needs and desires of consumers seem to be more diverse. It is caused by the various lifestyle of consumers. Therefore, marketers need to make a classification of consumers or which is called a market segmentation. Market segmentation is the activity for grouping heterogeneous market into smaller homogeneous market in order to form a product preference to the needs of significant market segments. Conventional segmentation tool, such as demographic segmentation is less effective in predicting consumer because of what is often called market fragmentation. Demographic variable is not enough to recognize consumers because marketers need to know the lifestyle of consumers. The concept of lifestyle segmentation as a result of psychographic segmentation group began to develop in the 1970s. Analysis of consumer lifestyle has become a very popular tool in research in the field of marketing.In 1993, the concept of new lifestyle-related products to a category of its achievement with cognitive-deductive system developed by Brunso, Grunert, and Bisp was begun from Market-Based Productand Process Development in Danish (MAPP) research group di Arhuss School ofBusiness.They applied to food by developing an approach to food-related lifestyle (FRL), which was focused as the concept of lifestyle approach to explore market segments related to food generally.